Pembangunan Sistem Aplikasi Pelayanan Administrasi Desa Berbasis Web dengan Fitur Notifikasi Sms Gateway (Studi Kasus Desa Pelangwot) - Anton Firdaus; Nurudin Santosa; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The public service is the principal task of the Government in his devotion to the community. As success yardstick, service administration and correspondence was supposed to be done well and quickly in order to deliver satisfaction value to society. But on its application of course there are some conditions that can become a constraint so that the Ministry can not be applied to the maximum. The village itself is one of the Pelangwot village in Lamongan which has an area of 6,767.824 km2, the distance between the village and the village office which can reach 3.5 km with the road conditions become unfavourable factors that lead to constraints for the community to be able to take care of the needs of administration in the Office of the village. See the problem is of course required the existence of a media that can bridge the communities in search of information sources at the same time maintaining the village administration. In this case the author developed a web-based media that can be used to make a booking letter, with the features of sms gateway to provide information to the public about the status of their mail messages. The system development process is done by using the waterfall model that produces four types of users, eighty-five functional needs, and one of the non-functional requirements. Testing is done at the level of the unit and validation, as well as there are also testing compatibility with 100% valid test results.